Mechanism of passvity breakdown of pure iron as compared to other metals - Galvele, José Rodolfo (Comisión Nacional de Energía Atómica; Argentina, 1975)
Fil: Galvele, José Rodolfo Comisión Nacional de Energía Atómica; Argentina